2017
DOI: 10.1093/eurpub/ckx081
|View full text |Cite
|
Sign up to set email alerts
|

How strongly related are health status and subjective well-being? Systematic review and meta-analysis

Abstract: Background: Health status is widely considered to be closely associated with subjective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
96
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(119 citation statements)
references
References 37 publications
15
96
1
7
Order By: Relevance
“…This study has also shown that being healthy is stronger correlated with both life satisfaction and happiness positively. This confirms a lot of studies done by Ngamaba, Panagioti, & Armitage (2017) and Friedman & Kern (2014) that being physically and psychologically healthy is correlated with people's SWB, individuals who have poor health have been reported to have poor subjective well-being. Moreover, married people have been reported to have good health compared to single people (Bulloch, Williams, Lavorato, & Patten, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This study has also shown that being healthy is stronger correlated with both life satisfaction and happiness positively. This confirms a lot of studies done by Ngamaba, Panagioti, & Armitage (2017) and Friedman & Kern (2014) that being physically and psychologically healthy is correlated with people's SWB, individuals who have poor health have been reported to have poor subjective well-being. Moreover, married people have been reported to have good health compared to single people (Bulloch, Williams, Lavorato, & Patten, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…As reported by the previous study, the association between health and SWB of individuals were statistically significant and positive, which mean by improving people's health, the government can improve the SWB of their citizens (Ngamaba, Panagioti, & Armitage, 2017). There is a bidirectional relationship between physical health and SWB, with SWB and health are also closely linked to age (Steptoe, Deaton, & Stoone, 2015).…”
Section: Health Religious Commitment and Spiritualitymentioning
confidence: 56%
“…The present results also suggest that self-rated health is an important determinant of multiple elements of positive wellbeing. Previous studies have found that subjective and/or self-related health tend to be closely associated with measures of individual wellbeing (Staptoe et al, 2015), although this hypothesis has not been fully tested and there is no consensus on what process can explain this relationship (Monden, 2014;Ngamaba, Panagioti, & Armitage, 2017). Maintaining good health increases the capacity of an older person to live independently, conduct activities of daily living, and perform other personal care activities and household work, which entail autonomy, reflected in the older person's psychological wellbeing (Celik, Celik, Hikmet, & Khan, 2017).…”
Section: Discussionmentioning
confidence: 99%